Corporate Social Responsibility Reporting And Financial Performance- A Study Of Nigerian Breweries Plc - Adesunloro, Babalola Raphael; Udeh, Francis Nnoli; Abiahu, Mary-Fidelis Chidoziem (Archives of Business Research, 2019)
To succeed in the business world, organisations must provide to their investors and host communities, evidence of reliable and credible efforts to ensure their safety in the light of their operations. This study aimed at ascertaining to what extent and effect corporate social responsibility reporting has had on the performance of Nigerian Breweries Plc. Descriptive research design was adopted in conducting the study. A sample of 355 respondents drawn the staff of Nigerian Breweries Plc and using content analysis of the financial statement of Nigerian Breweries Plc in comparism with three purposefully selected Nigerian banks namely First Bank Plc, United Bank for Africa and Fidelity Bank Plc and structured questionnaires designed to seek information on the effect of corporate social responsibility reporting on performance of corporate organisations, the study made use of the t-test statistics at 5% level of significance to analyse data collected for the study. Findings from the study show that Nigerian Breweries Plc has not significantly disclosed her social responsibility accounting information as contained in the Annual Reports and Accounts of Nigerian Breweries Plc 2014-2017 as compared to other companies in Nigeria. However, it was discovered that the corporate social responsibility reports of Nigerian Breweries Plc has enhanced the financial performance of the company comparatively. This goes to imply that Nigerian Breweries Plc performance is positively influenced by its social responsibility culture. The study therefore recommends that Nigerian Breweries Plc as well as other Nigerian manufacturing companies should put in more efforts towards improving the lot of their stakeholders through adequate disclosure of corporate social responsibility information in their annual reports and accounts. It is recommended that management of Nigerian Breweries Plc should streamline its corporate social responsibilities on activities that will improve the company’s image and as well enhance the financial performance of the company